The gunfighter [videorecording (DVD)] - Bowers, William, 1916-1987; Sellers, William; Peck, Gregory, 1916-2003; Westcott, Helen, 1928-1998; Mitchell, Millard, 1900-1953; Parker, Jean; Malden, Karl; Homeier, Skip; Ross, Anthony, 1906-1955; Felton, Verna, 1890-1966; Corby, Ellen; Jaeckel, Richard, 1926-1997; et al. (Criterion collection, 2020)
A key forerunner of the new breed of dark, brooding westerns that would cast a shadow over America's frontier folklore, this subversive psychological saga sounds a death knell for the myth of the outlaw hero. In one of his most morally complex roles, Gregory Peck stars as Jimmy Ringo, an infamous gunslinger looking to hang up his holsters and start a new life, but whose reputation draws him inexorably into a cycle of violence and revenge from which he cannot escape.